2023
DOI: 10.1513/annalsats.202209-793oc
|View full text |Cite
|
Sign up to set email alerts
|

One Year Later: Family Members of Patients with COVID-19 Experience Persistent Symptoms of Posttraumatic Stress Disorder

Abstract: Rationale Family members of critically ill patients with coronavirus disease (COVID-19) have described increased symptoms of posttraumatic stress disorder (PTSD). Little is known about how these symptoms may change over time. Objectives We studied changes in PTSD symptoms in family members of critically ill patients with COVID-19 over 12 months. Methods This prospective, multisite observational cohort study recruited participants at 12 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Most existing studies among adults focus on symptom trajectories for PGD, 12 , 13 , 14 , 15 , 16 , 17 PTSD, 18 , 19 , 20 , 21 and depression 22 , 23 , 24 , 25 , 26 individually without considering concurrent changes in emotional distress from bereavement and traumatic events. However, distressed psychological grief reactions cooccur as the norm rather than the exception, 27 and resilience in 1 outcome (eg, PGD) may often coexist with deficits in other important outcomes (eg, PTSD or depression).…”
Section: Introductionmentioning
confidence: 99%
“…Most existing studies among adults focus on symptom trajectories for PGD, 12 , 13 , 14 , 15 , 16 , 17 PTSD, 18 , 19 , 20 , 21 and depression 22 , 23 , 24 , 25 , 26 individually without considering concurrent changes in emotional distress from bereavement and traumatic events. However, distressed psychological grief reactions cooccur as the norm rather than the exception, 27 and resilience in 1 outcome (eg, PGD) may often coexist with deficits in other important outcomes (eg, PTSD or depression).…”
Section: Introductionmentioning
confidence: 99%
“…This echoes an earlier study of ICU families conducted in 2020 that found that the prevalence of significant PTSD symptoms at 3 months was also 64% ( 3 ). Although the authors had previously reported that PTSD is highly prevalent among ICU family members at 3 months, the new study ( 1 ) reveals that the impact on many family members is sustained far beyond the ICU stay. Worse, although methodological differences make a direct comparison difficult, studies conducted before the pandemic reported prevalences of significant PTSD symptoms in ICU families of only 14% at discharge ( 4 ) and 19% at 3-month follow-up ( 5 ).…”
mentioning
confidence: 85%
“…In this issue of AnnalsATS , there are two prospective cohort studies that assessed mental health symptoms in family members of adult intensive care unit (ICU) patients with COVID-19 in 2020 ( 1 , 2 ). Ambler and colleagues (pp.…”
mentioning
confidence: 99%
See 2 more Smart Citations